Research Progress on Catalysts for Pyrolysis and Gasification of Organic Solid Waste - Jianzhi YANG; Haitao CHEN; Xing ZHU; Min LIN (能源环境保护)
The production of high-value-added fuel products through the pyrolysis gasification of organic solid waste facilitates the transformation of waste into valuable resources and promotes efficient resource recycling. This technology provides a viable approach to environmental pollution control and contributes to the achievement of the "dual-carbon" goals of carbon peaking and carbon neutrality. The pyrolysis gasification process is both environmentally sustainable and highly energy-efficient. It significantly reduces waste volume, positioning it as a critical technology in contemporary organic solid waste management. Catalysts play a crucial role in this process, and understanding their performance and underlying mechanisms is essential for advancing pyrolysis gasification technology. Current research identifies several catalysts employed in pyrolysis gasification, including carbonates, metal oxides, monometallic catalysts, monatomic catalysts, biochar, and molecular sieves. The incorporation of catalysts effectively modulates the activation energy of the reaction and alters its microenvironment, such as acid/base sites and electron coordination, thereby enhancing product conversion and selectivity. Their mechanisms of action primarily involve: (1) reducing the activation energy required for chemical bond cleavage in organic molecules, thus accelerating the decomposition of the organic molecular structure under relatively mild conditions; (2) optimizing the reaction pathway to improve product selectivity and conversion; and (3) modulating the catalytic microstructure to increase active sites and enhance catalytic performance. These mechanisms collectively enhance the catalytic efficiency of pyrolysis gasification, leading to higher yields of combustible gases (e.g., H2, CO, and CH4) and liquid fuels, thereby optimizing the utilization of organic solid waste resources. Simultaneously, tar formation can be effectively reduced, thereby preventing equipment clogging and environmental pollution. Extensive research and experimental validation demonstrate the efficacy of catalysts in optimizing reaction conditions, refining reaction pathways, minimizing byproducts, and enhancing energy conversion. This provides a theoretical basis and practical guidance for optimizing pyrolysis gasification technology. Furthermore, given the large volume, compositional complexity, varied reaction pathways, and dispersed nature of organic solid waste, integrating machine learning with pyrolysis gasification can facilitate rapid waste characterization, precise catalytic optimization, and significant improvements in resource utilization. This synergy enhances process adaptability and resource efficiency while addressing the challenges of variable feedstocks. Finally, this study summarizes and envisions the integration of new technologies with pyrolysis gasification catalytic conversion, which is anticipated to enable innovative integration, multifaceted utilization, and intelligent optimization, further improving resource conversion efficiency and environmental benefits.